How teacher emotional support motivates students: The mediating roles of perceived peer relatedness, autonomy support, and competence. (April 2016) - Ruzek, Erik A.; Hafen, Christopher A.; Allen, Joseph P.; Gregory, Anne; Mikami, Amori Yee; Pianta, Robert C.
Abstract: Multilevel mediation analyses test whether students' mid-year reports of classroom experiences of autonomy, relatedness with peers, and competence mediate associations between early in the school year emotionally-supportive teacher-student interactions (independently observed) and student-reported academic year changes in mastery motivation and behavioral engagement. When teachers were observed to be more emotionally-supportive in the beginning of the school year, adolescents reported academic year increases in their behavioral engagement and mastery motivation. Mid-year student reports indicated that in emotionally-supportive classrooms, adolescents experienced more developmentally-appropriate opportunities to exercise autonomy in their day-to-day activities and had more positive relationships with their peers. Analyses of the indirect effects of teacher emotional support on students' engagement and motivation indicated significant mediating effects of autonomy and peer relatedness experiences, but not competence beliefs, in this sample of 960 students (ages 11–17) in the classrooms of 68 middle and high school teachers in 12 U.S. schools. Highlights: We used observations and student reports to understand effects of classroom climate. Observed emotionally-supportive instruction motivated and engaged adolescents. Students' experiences of autonomy and peer relatedness mediate these associations. Given its broad influence, teacher emotional support can be a target of intervention.